2017
DOI: 10.1371/journal.pone.0179839
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of GII norovirus in hospitalized children with acute diarrhea, in Beijing

Abstract: This study was addressed to the relationship between norovirus and acute diarrhea in hospitalized children, including hospital-acquired infection (HAI) and community-acquired infection (CAI) in a children's hospital in Beijing. RT-PCR was used to detect norovirus in stool specimen, followed by sequence analysis for PCR products. From 2010 to 2013, a total of 1248 specimens, including 661 from the HAI group and 587 from the CAI group were tested for norovirus. Norovirus were detected in 380 of 1248 (30.4%) diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
4
6
0
Order By: Relevance
“…The worldwide reported prevalence of norovirus among fecal samples from pediatric patients with acute sporadic gastroenteritis has a broad range, depending on whether patients have been hospitalized or not, the ages of the children, and the methodology that has been used (10). Norovirus infection is characterized by nausea, vomiting abdominal cramps and diarrhea without blood (33). In this study, abdominal pains, vomiting, fever, watery diarrhea, and dehydration were the most common particular symptoms in patient with norovirus infections, almost similar to previously reported study.…”
Section: Discussionsupporting
confidence: 89%
“…The worldwide reported prevalence of norovirus among fecal samples from pediatric patients with acute sporadic gastroenteritis has a broad range, depending on whether patients have been hospitalized or not, the ages of the children, and the methodology that has been used (10). Norovirus infection is characterized by nausea, vomiting abdominal cramps and diarrhea without blood (33). In this study, abdominal pains, vomiting, fever, watery diarrhea, and dehydration were the most common particular symptoms in patient with norovirus infections, almost similar to previously reported study.…”
Section: Discussionsupporting
confidence: 89%
“…A recent cohort study of 8.5 years was conducted at Texas Children’s Hospital which showed a 60–87% decrease in rotavirus infection post vaccine licensure . This study helps confirm that noroviruses are quickly replacing rotaviruses as the leading cause of acute gastroenteritis in both immunocompetent and immunocompromised patients owing to the recent development and universal distribution of a rotavirus vaccine. , According to a report from the Centers for Disease Control and Prevention (CDC), it is now estimated that noroviruses are responsible for 685 million cases each year with an estimated $60 billion medical and socioeconomic cost . Specifically, the GII.4 norovirus genotype accounts for more than 50% of all outbreaks worldwide. ,, This overwhelming global burden drives the need for identification and characterization of potential norovirus targets to exploit for drug design and development …”
mentioning
confidence: 74%
“…1 This study helps confirm that noroviruses are quickly replacing rotaviruses as the leading cause of acute gastroenteritis in both immunocompetent and immunocompromised patients owing to the recent development and universal distribution of a rotavirus vaccine. 2,3 According to a report from the Centers for Disease Control and Prevention (CDC), it is now estimated that noroviruses are responsible for 685 million cases each year with an estimated $60 billion medical and socioeconomic cost. 4 Specifically, the GII.4 norovirus genotype accounts for more than 50% of all outbreaks worldwide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, different studies showed the prevalence of this pathogen to be up to 35.2% in sporadic outbreaks of acute gastroenteritis in children under five-years-old (30). Indeed, the GII genogroup has been found in up to 92% of the analyzed samples in other countries (30)(31)(32), which represents a latent risk due to this virus incidence increase among children younger than five-years-old after the application of the rotavirus vaccine (33). Furthermore, the analysis revealed the presence of genotypes HAstV-1 and HAstV-3, indicating a high prevalence of astroviruses in this region, which is in line with reports from other countries (24,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%